NILAI EKONOMI JASA LINGKUNGAN LAHAN SAWAH DI KABUPATEN BOYOLALI - Adhistie Fadila Setyaputri; Danila Desti Ramadhani; Vania Maharani Rizky Pratiwi (Yayasan Nusantara Hasana Berdikari, 2023)
Boyolali Regency is one of the largest rice suppliers in Central Java, with its harvested area fluctuating due to the conversion of paddy fields to non-rice fields. However, this change did not significantly affect rice productivity and production due to the use of upland rice varieties that can grow on dry land. The economic value of paddy fields is not only limited to aspects of crop production or the market value of crops, but also includes the ecological, social and cultural benefits associated with the use of paddy fields. In this study, an economic valuation approach was used to measure the economic value of paddy fields which includes these aspects. This research shows the importance of maintaining the economic value of paddy fields as an important asset in rice production and providing employment. Efforts to conserve paddy fields and develop rice varieties that are suitable for land conditions need to be continued to ensure the sustainability of rice production and adequacy of employment opportunities in Boyolali Regency.